PENGARUH KOMUNIKASI TERAPEUTIK PERAWAT TERHADAP TINGKAT KECEMASAN ORANG TUA PASIEN SEBELUM TONSILEKTOMI - Kio, Alfiery Leda; Artana, I Wayan; Mastini, Ni Luh Putu (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2020)
Inflammation of the tonsils either caused by viruses or bacteria that cause acute tonsillitis if not experiencing complete healing can develop into chronic tonsillitis. The action that is often done in chronic tonsillitis is tonsillectomy. The management of tonsillectomy has psychological consequences on the patient and his family including anxiety. Anxiety can be reduced by nursing actions that focus on therapeutic communication for patients and their families. Objective: The study aims to determine the effect of nurses' therapeutic communication on the anxiety level of parents of patients before tonsillectomy in Mangusada Badung Hospital. Method: The design used was pre experimental pre-post desing test. The sample is the parent of the patient who is going to undergo a tonsillectomy. Data were collected using a HARS questionnaire before and after therapeutic communication. Data were analyzed using the Wilcoxon Test. Results: The results of the study of the average respondent had a moderate level of anxiety before therapeutic communication and the level of anxiety decreased after therapeutic communication. Conclusion: of the research is that there is a significant and significant effect of therapeutic communication on the reduction of respondents' anxiety levels before their children undergo tonsillectomy at the Mangusada Badung Regional Hospital p (0.001 <? 0.05).